THE EFFECT OF Theileria INFECTION ON THE IMMUNE RESPONSES OF CATTLE TO RINDERPEST VACC - Al-Gabban, M.G.; Barhoom, S.Sh.; Al-Banna, A.S. (The Iraqi Journal of Veterinary Medicine, 1996)
Immune responses to rinderpest virus vaccine were studied in 25 calves (3-months old) naturally infected with Theilria and non-infected 25 calves (3-months old) as control group. The immune responses to rinderpest virus vaccine before vaccination and 21 days post-vaccination were examined by serum neutralization test on tissue culture. The results indicated that calves affected with theileriasis showed diminished level of antibodies after 21 days post-vaccination with rinderpest virus vaccine in comparisons with those of the Theileria non-infected calves